Transmembrane dislocases: a second chance for protein targeting. Issue 11 (November 2021) - Dederer, Verena; Lemberg, Marius K.
Abstract : Precise distribution of proteins is essential to sustain the viability of cells. A complex network of protein synthesis and targeting factors cooperate with protein quality control systems to ensure protein homeostasis. Defective proteins are inevitably degraded by the ubiquitin-proteasome system and lysosomes. However, due to overlapping targeting information and limited targeting fidelity, certain proteins become mislocalized. In this review, we present the idea that transmembrane dislocases recognize and remove mislocalized membrane proteins from cellular organelles. This enables other targeting attempts and prevents degradation of mislocalized but otherwise functional proteins. These transmembrane dislocases can be found in the outer mitochondrial membrane (OMM) and endoplasmic reticulum (ER). We highlight common principles regarding client recognition and outline open questions in our understanding of transmembrane dislocases. Highlights: Limited fidelity of protein-targeting machineries results in low-level mislocalization of proteins, which are commonly recognized by protein quality control factors and degraded by the cytoplasmic proteasome. Protein dislocation from mitochondria and the endoplasmic reticulum (ER) into the cytoplasm can feed mislocalized proteins back into the targeting systems, protecting them from degradation while correcting mislocalization errors. Genetic and cellular analyses define the ATPase associated with diverse cellular activities (AAA)-ATPases Msp1 as a major protein dislocase of the outer mitochondrial membrane. Cryo-electron microscopy structure determination and biochemical analysis of the P5-type ATPase Spf1 revealed a previously unappreciated role in protein extraction from the ER membrane. Protein dislocases are intertwined with classical protein quality control systems to maintain protein homeostasis.